Prediction of thiopurine failure in pediatric Crohn's disease: pediatric IBD Porto group of ESPGHAN - Lerchova, Tereza; Hradsky, Ondrej; Kulich, Michal; Veres, Gabor; Dias, Jorge Amil; Sładek, Małgorzata; Kolacek, Sanja; Van Biervliet, Stephanie; Melek, Jan; Serban, Daniela E; Winther, Katrine; de Meij, Tim; et al. (Pediatric research, 2023)
BACKGROUND: Maintaining of remission early in the disease course of Crohn's disease (CD) is essential and has major impact on the future prognosis. This study aimed to identify baseline predictors to develop model allowing stratification of patients who will not benefit from long-term azathioprine (AZA) treatment and will require more intensive therapy. METHODS: This study was designed to develop clinical prediction rule using retrospective data analysis of pediatric CD patients included in prospective inception cohort. Clinical relapse was defined as necessity of re-induction of remission. Sequence of Cox models was fitted to predict risk of relapse. RESULTS: Out of 1190 CD patients from 13 European centers, 441 were included, 50.3% patients did not experience clinical relapse within 2 years of AZA treatment initiation. Median time to relapse was 2.11 (CI 1.59-2.46) years. Of all the tested parameters available at diagnosis, six were significant in multivariate analyses: C-reactive protein (p = 0.038), body mass index Z-score >0.8 SD (p = 0.002), abnormal sigmoid imaging (p = 0.039), abnormal esophageal endoscopy (p = 0.005), ileocolonic localization (p = 0.023), AZA dose in specific age category (p = 0.031). CONCLUSIONS: Although the possibility of predicting relapse on AZA treatment appears limited, we developed predictive model based on six baseline parameters potentially helpful in clinical decision. IMPACT: The possibility of predicting relapse on AZA treatment appears to be possible but limited. We identified six independent predictors available at diagnosis of early AZA/6-MP treatment failure in pediatric CD patients. Using combination of these factors, a model applicable to clinical practice was created. A web-based tool, allowing estimation of individual relapse risk in pediatric CD patients on a particular therapeutic regimen, has been developed.
Keywords: Crohn Disease; Child; Remission Induction; Recurrence; dítě; Crohnova nemoc; Retrospective Studies; retrospektivní studie; lidé; Immunosuppressive Agents; Prospective Studies; Azathioprine; indukce remise; Humans; recidiva; imunosupresiva; azathioprin; prospektivní studie